THE EFFECT OF HYBRID LEARNING INTEREST AND MOTIVATION ON INDONESIAN LANGUAGE LEARNING - Hidayat, Ryan; Santosa, Prima Pantau Putri (Universitas Negeri Makassar, 2024)
This study aims to determine the effect of interest and motivation in hybrid learning on the learning outcomes of Indonesian language courses. The method used in this research is quantitative. The population of this study were all students of Indraprasta PGRI University. The sampling technique used was simple random sampling. The number of samples in this study was 88. The hybrid learning interest and motivation instruments have been validated. Quantitative data analysis tested the significance of the regression coefficient and calculated the regression line equation. The results revealed that the application of hybrid learning interests and motivations had significant effects on learning outcomes. This finding can be seen from the results of the t test. It can be seen that the Sig value is 0.000 and Fhitung is 19.682, while Ftabel is 3.104, so the Sig value is < 0.05 and Fhitung > Ftabel, or regression significance. The paradigm of emphasizing motivation for students has an effect on students' ability to learn.